Models, frameworks and theories in the implementation of programs targeted to reduce formal coercion in mental health settings: a systematic review - Lantta, Tella; Duxbury, Joy; Haines-Delmont, Alina; Björkdahl, Anna; Husum, Tonje Lossius; Lickiewicz, Jakub; Douzenis, Athanassios; Craig, Elaine; Goodall, Katie; Bora, Christina; Whyte, Rachel; Whittington, Richard (Frontiers in Psychiatry, 2023)
Introduction: Implementation models, frameworks and theories (hereafter tools) provide researchers and clinicians with an approach to understand the processes and mechanisms for the successful implementation of healthcare innovations. Previous research in mental health settings has revealed, that the implementation of coercion reduction programs presents a number of challenges. However, there is a lack of systematized knowledge of whether the advantages of implementation science have been utilized in this field of research. This systematic review aims to gain a better understanding of which tools have been used by studies when implementing programs aiming to reduce formal coercion in mental health settings, and what implementation outcomes they have reported. Methods: A systematic search was conducted using PubMed, CINAHL, PsycINFO, Cochrane, Scopus, and Web of Science. A manual search was used to supplement database searches. Quality appraisal of included studies was undertaken using MMAT - Mixed Methods Appraisal Tool. A descriptive and narrative synthesis was formed based on extracted data. Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines were followed in this review. Results: We identified 5295 references after duplicates were removed. Four additional references were found with a manual search. In total 8 studies were included in the review. Coercion reduction programs that were implemented included those that were holistic, and/or used professional judgement, staff training and sensory modulation interventions. Eight different implementation tools were identified from the included studies. None of them reported all eight implementation outcomes sought from the papers. The most frequently reported outcomes were acceptability (4/8 studies) and adaptation (3/8). With regards to implementation costs, no data were provided by any of the studies. The quality of the studies was assessed to be overall quite low. Discussion: Systematic implementation tools are seldom used when efforts are being made to embed interventions to reduce coercive measures in routine mental health care. More high-quality studies are needed in the research area that also involves perspectives of service users and carers. In addition, based on our review, it is unclear what the costs and resources are needed to implement complex interventions with the guidance of an implementation tool.